Hypophosphatemia in a Malnourished Child: When Renal Fanconi Syndrome Does Not Stand for Refeeding Syndrome. Issue 1 (10th May 2018) - Runde, Joseph; Rivera‐Rivera, Edgardo; Pompeii‐Wolfe, Cecelia; Clardy, Christopher; Sentongo, Timothy
Abstract: Refeeding syndrome is diagnosed based on the onset of multiple laboratory abnormalities (most commonly hypophosphatemia) and clinical signs in the setting of nutrition rehabilitation of malnourished patients. Because definitions are not uniform, a broad differential diagnosis should always include renal tubular dysfunction. Our report details a 3 year‐old child with undiagnosed renal tubular dysfunction who presented with the clinical picture of refeeding syndrome with refractory electrolyte abnormalities. A diagnosis of renal Fanconi syndrome was made after urinalysis that revealed glucosuria and urine electrolyte losses. Thus, urinalysis can aid in making a positive diagnosis of refeeding syndrome.